Family Business as Paradox - Schuman, A.; Stutz, S.; Ward, J.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
Rather than having to choose between the family and the business, the authors argue that if family-owned businesses can consciously manage and over time, perhaps, synthesize these contradictions, the Family Enterprise will have a long-term strategic and competitive advantage and the family will remain committed to continuity.
Keywords: Leadership; Small business; Management; Family-owned business enterprises; Business Strategy/Leadership.; Small Business; Management; Family Business